2008
DOI: 10.1007/s00125-008-1148-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with a modest increase in inflammation in subcutaneous adipose tissue of moderately obese women

Abstract: Aims/hypothesis We have previously described differences in adipose cell size distribution and expression of genes related to adipocyte differentiation in subcutaneous abdominal fat obtained from insulin-sensitive (IS) and -resistant (IR) persons, matched for degree of moderate obesity. To determine whether other biological properties also differ between IR and IS obese individuals, we quantified markers of inflammatory activity in adipose tissue from overweight IR and IS individuals. Methods Subcutaneous abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 21 publications
12
49
1
Order By: Relevance
“…These findings are consistent with independent reports of reduced adipogenesis in insulinresistant patients (Goedecke et al, 2011;Yang et al, 2004). Furthermore, these expression changes were also associated with modest increases in inflammatory activity in insulin-resistant AT (McLaughlin et al, 2008). As the presence of small adipocytes in both VAT and SAT appears to be correlated with increased hypertrophy of larger adipocytes in abdominal SAT (Liu et al, 2009), these findings could be interpreted as suggesting that SAT is the primary site for lipid accumulation; however, once a maximal SAT adipocyte size is reached, hyperplastic growth is initiated in both VAT and SAT.…”
Section: Regional Variation In Adipose Morphologysupporting
confidence: 92%
“…These findings are consistent with independent reports of reduced adipogenesis in insulinresistant patients (Goedecke et al, 2011;Yang et al, 2004). Furthermore, these expression changes were also associated with modest increases in inflammatory activity in insulin-resistant AT (McLaughlin et al, 2008). As the presence of small adipocytes in both VAT and SAT appears to be correlated with increased hypertrophy of larger adipocytes in abdominal SAT (Liu et al, 2009), these findings could be interpreted as suggesting that SAT is the primary site for lipid accumulation; however, once a maximal SAT adipocyte size is reached, hyperplastic growth is initiated in both VAT and SAT.…”
Section: Regional Variation In Adipose Morphologysupporting
confidence: 92%
“…Data on ATM gene expression in the context of the metabolic complications of obesity are limited. Expression of five inflammatory genes in SAT was shown to be different between insulinresistant and insulin-sensitive overweight patients [25]. In our study, we found significantly increased mRNA levels of 24 ATM-specific markers in the metabolic syndrome patients compared with all other groups in both fat depots.…”
Section: Discussionsupporting
confidence: 49%
“…While these data could not be obtained due to the modest amount of adipose tissue material, it would have been interesting to correlate these variables with gene expression data of ATM-specific markers. In fact, it has been shown that an increased proportion of small adipose cells is associated with inflammation in SAT [25]. In addition, because various subpopulations of macrophages may exist and express distinct surface markers depending on the local microenvironment, different ATM markers could be identified in different macrophage subpopulations of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One proposed mechanism is that obesity is associated with a prothrombotic and proinflammatory state. [328][329][330][331][332] BMI is directly associated with fibrinogen, factor VII, plasminogen activator inhibitor, and tissue-type plasminogen activator antigen levels in both men and women. 328 Similar associations are present between abdominal obesity and hemostatic factors.…”
Section: Pathophysiologic Mechanisms Of Obesity Abdominal Adipositymentioning
confidence: 99%